The Mechanisms of The Toxic Effect of Intrauterine and Early Postnatal Exposure to Pesticides on The Development of The Immune System of Offspring - Bakhodirovna, Zokirova Nargiza (American Journal of Biomedicine and Pharmacy, 2026)
Abstract: The aim of the study was to identify the toxic effect of intrauterine and early postnatal exposure to pesticides on the development of the endocrine and immune system of offspring. The experiments were performed on white adult male rats, who respectively received pesticides lambda-cyhalothrin or fipronil during pregnancy and lactation. Progeny from experimental and control animals was studied on the 3rd, 7th, 14th, 21st and 30th days after birth using methods of morphology, electron microscopy, immunohistochemistry and biochemistry. It has been shown that the toxic effect of pesticide exposure during pregnancy and lactation is manifested in the form of growth retardation and formation of the thymus, lymph nodes, spleen and thyroid glands of offspring. In the mechanism of toxic effect of pesticides on the immune-endocrine system, the leading role is played by the imbalance between proliferation and apoptosis of cells, caused both by direct toxic effects of drugs, both developing hypothyroidism and oxidative stress in mother and offspring. This causes the need for early detection of hypothyroidism and oxidative stress in pregnant women and newborns, followed by their pharmacological correction.